Presoja varovalnega učinka gozda pred snežnimi plazovi - Pintar, Simon (Acta silvae et ligni, 2016)
The road leading to the Vršič Pass is threatened by snow avalanches, and the forests above it are performing a protective function against them. We analysed potential hazard to the road and forests above it from snow avalanches, and evaluated the protective function of the forest. We defined guidelines and measures for further development of the forest to enhance its protective effect, and evaluated the actual spatial distribution of formalized protective function area of the forest within management plans. We set a network of 21 research sample plots. Using the modified method NaiS (Frehner et al., 2005), we defined the stand boundaries, analysed them and compared the actual state of the stands to the target situation. With regard to the slope and forest cover, we made a map of the sections most prone to formation of snow avalanches. We concluded that none of the stands provided complete and permanent protective function against snow avalanches. The greatest problems lay in poor regeneration and lack of unevenaged stand structure. The most important guidelines for the future development of the forest are favouring heterogeneous stand structure and regeneration, safeguarding good stability and vitality of the trees and providing for their sufficient density.
Keywords: protective forest; varovalni gozdovi; varovalna funkcija gozdov; protective forest function; zaščitna funkcija gozdov; snow avalanche; management of protective forests; snežni plazovi; guidelines for forest management; upravljanje varovalnih gozdov; silviculture of protective forest; smernice za upravljanje z gozdovi; gojenje varovalnih gozdov